Analysis of the biorelevance of the main methods used to compare in vitro dissolution profiles - Ruiz, María Esperanza (2013)
The article analyzes comparatively the performance of the main methods proposed for the comparison of percent dissolved vs. time curves: model-dependent, model-independent and ANOVA-based statistical methods. In particular, it discusses the biorelevance of those methods when applied for the comparison of dissolution profiles of multisource drug products. As a conclusion, the use of a combined-approach between model-independent methods are encouraged, based on the analysis of in vitro dissolution profiles of several brands of oral solid dosage forms of different drugs and on the comparison of those results with previously published in vivo results.